Huyền thoại về một vùng đất - Nguyễn-văn-Kim (Nhà xuất bản Khoa học xã hội, 2021)
Cultural space of the Central Highlands through the Ede epic
Includes bibliographical references (pages 277-291) and index
Keywords: Rhadé; Minderheit; Mittelvietnam; Versdichtung